circ_NOTCH3 Functions as a Protooncogene Competing With miR-205-5p, Modulating KLF12 Expression and Promoting the Development and Progression of Basal-Like Breast Carcinoma - Guan, Bing; Li, Qing; Zhang, Hui-Zhen; Yang, Hai-Sheng (Frontiers in Oncology, 2021)
Breast cancer is the most common type of cancer diagnosed among women, and basal-like breast carcinoma (BLBC) has been associated with a more aggressive histology, poorer prognosis, and non-responsiveness to hormone therapy. In the present study, the role and molecular mechanism of circular (circ)_NOTCH3 in the development and progression for BLBC was identified. circ_RNAs array was used to screen the ectopic expression of hsa_circ_0109177 (circ_NOTCH3) in BLBC. RT-qPCR was conducted to evaluate the circ_NOTCH3 expression in BLBC tissues and paired normal tissues, as well as related cell lines. Cell function changes were analyzed following circ_NOTCH3 or micro (mi)RNA overexpression or co-expression. Bioinformatics analysis and dual-luciferase reporter assay were performed to predict and verify the binding sites between circ_NOTCH3 and miRNAs. Gene expression changes were assessed using western blotting. circ_NOTCH3 had a significantly higher expression in BLBC tissues and cell lines. The upregulation of circ_NOTCH3 promoted the proliferation, migration, invasion and inhibited the apoptosis for BLBC cells. The opposite results were observed following miR-205-5p overexpression. However, the co-expression of circ_NOTCH3 and miR-205-5p resulted in those restoration. circ_NOTCH3 is capable of binding to miR-205-5p, and upregulating its target gene KLF12, which can be downregulated by miR-205-5p overexpression and restored by the co-expression of circ_NOTCH3 and miR205-5p. circ_NOTCH3, being an protooncogene and a powerful biomarker, can function as a sponge, compete with miR-205-5p, modulate KLF12 expression, and promote the development and progression of BLBC.